2012
DOI: 10.1093/gbe/evs101
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Rate and Duplicability in the Arabidopsis thaliana Protein–Protein Interaction Network

Abstract: Genes show a bewildering variation in their patterns of molecular evolution, as a result of the action of different levels and types of selective forces. The factors underlying this variation are, however, still poorly understood. In the last decade, the position of proteins in the protein–protein interaction network has been put forward as a determinant factor of the evolutionary rate and duplicability of their encoding genes. This conclusion, however, has been based on the analysis of the limited number of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
49
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 95 publications
5
49
1
Order By: Relevance
“…2002; Hahn and Kern 2005; Lemos et al 2005; Chakraborty et al . 2010, 2011; Alvarez-Ponce and Fares 2012). Similar trend has been also observed in our core/attachment data set (Spearman’s ρ connectivity vs .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2002; Hahn and Kern 2005; Lemos et al 2005; Chakraborty et al . 2010, 2011; Alvarez-Ponce and Fares 2012). Similar trend has been also observed in our core/attachment data set (Spearman’s ρ connectivity vs .…”
Section: Resultsmentioning
confidence: 99%
“…According to this proposal, it has been demonstrated that essential genes evolve slower than the genes which are dispensable (Jordan et al 2002). Moreover, proteins those interact with a large number of partners evolve at a slower rate compared with the proteins with fewer number of interacting partners (Hirsh and Fraser 2001; Jordan et al 2002; Fraser et al 2003; Hahn and Kern 2005; Lemos et al 2005; Chakraborty et al 2011; Alvarez-Ponce and Fares 2012). However, these results have been questioned by some researchers (Batada et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the strong correlation between gene duplicability and gene function observed here, it remains to be further investigated which evolutionary mechanisms are responsible for the observed strong bias in duplicate retention patterns, and it remains to be established whether gene function directly influences gene duplicability or whether biased gene retention could be a by-product of other evolutionary phenomena instead, such as for instance the preservation of intermolecular interactions (dosage balance) or sequence constraints related to high levels of gene expression (Davis and Petrov, 2004;Drummond and Wilke, 2008). In particular, since network structure is often believed to constrain protein evolution and to underlie complex phenotypic traits, future work into this direction might benefit from investigating gene duplicability in a network context (Bekaert et al, 2011;D'Antonio and Ciccarelli, 2011;Alvarez-Ponce and Fares, 2012;Chae et al, 2012;Conant, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…To gain insight into the evolution of molecular systems, much research has been devoted to relating evolutionary properties of the genes, such as their substitution rates or detectable events of selection, with measures of their position and role within the system in which they participate, generally through its representation as a network. This approach of assessing molecular systems as networks has revealed that a significant, although small, part of the variation in the evolutionary rates of the genes can be explained by their position within the network (Fraser et al ; Papp et al ; Hahn and Kern ; Kim et al ; Greenberg et al ; Jovelin and Phillips ; Alvarez‐Ponce ; Alvarez‐Ponce and Fares ). However, biological interpretation of position within networks and its significance from an evolutionary point of view has largely remained obscure.…”
mentioning
confidence: 99%